Neopterin-inhibitor of dihydrofolate reductase and hypothetical action in the human body - Olszewski, Jan; Samborski, WÅ‚odzimierz; Bartkowiak, SÅ‚awomir (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Concentration of neopterin in the organism increases during many diseases and therefore it is used as a marker to assess the severity of these disease, applied treatment severity, oxidative stress and the cellular immune response. In this paper we attempt to determine the new properties of neopterin and its hypothetical role in DHFR activity in the human body. During the study we worked with neopterin by SIGMA, purity ‰¥ 98% (HPLC), and a set of reagents to determine the activity of dihydrofolate reductase. The study was performed using a spectrophotometer at a wavelength of Î» = 340 nm. The obtained results have confirmed that neopterin inhibits the activity of DHFR, both when it is fully dissolved in 1 N HCl as a suspension in a buffer (pH = 7.5) and as a supernatant. DHFR inhibition depends on the neopterin concentration in the reaction mixture. The results of our research and our discovery of new properties of neopterin as a DHFR inhibitor allow us to determine the hypothetical importance of neopterin in the body’s defence system.